Experimental study on shear performance of saw-tooth rock joint with weak interlayer under different moisture contents and filling degrees - Luo, Zhanyou; Zhang, Yufan; Du, Shigui; Huang, Man; Lyu, Yuanjun (Frontiers in Earth Science, 2023)
Weak interlayer is an important factor affecting the stability of rock joint, and the stability of rock joint has an important impact on natural disasters such as landslides. Scholars have conducted a large number of studies on the shear performance of rock joint with weak interlayer, but the research on the coupling factors of moisture content and filling degree of weak interlayer needs to be further deepened. In this paper, the 3D carving technology is used to produce the consistent serrated rock joint. Then, the ratio of common components of weak interlayer is studied, and the weak interlayer is obtained, which is similar to that in the field. Then, the saw-tooth rock joint samples with different moisture contents and filling degrees of weak interlayer are produced by the dry weight constant weight method. Finally, the shear strength test of different filling degree and moisture content of rock joint with weak interlayer under multi-level normal stress is carried out by using the self-developed direct shear apparatus for rock joint with weak interlayer. The test results show that the peak shear strength of rock joint with weak interlayer surface increases first and then decreases with the increase of moisture content. When the weak interlayer reaches the optimum moisture content, the peak shear strength reaches the maximum . The peak shear strength of rock joint with weak interlayer surface first increases and then tends to be stable with the increase of filling degree. When the filling degree reaches the critical filling degree, the peak shear strength tends to be stable. When the filling degree of weak interlayer is small and large, the saw-tooth rock joint shows shear dilatation and shear contraction in the shear process. The peak shear strength of rock joint with weak interlayer increases with the increase of normal stress.